If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 20x + 23y + 24z = 185 Solving 20x + 23y + 24z = 185 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-23y' to each side of the equation. 20x + 23y + -23y + 24z = 185 + -23y Combine like terms: 23y + -23y = 0 20x + 0 + 24z = 185 + -23y 20x + 24z = 185 + -23y Add '-24z' to each side of the equation. 20x + 24z + -24z = 185 + -23y + -24z Combine like terms: 24z + -24z = 0 20x + 0 = 185 + -23y + -24z 20x = 185 + -23y + -24z Divide each side by '20'. x = 9.25 + -1.15y + -1.2z Simplifying x = 9.25 + -1.15y + -1.2z
| -3(t-4)+9t=8t-3 | | x=.1(50+x) | | 7(x-10)=20-9x | | 2z+6+11z+7=90 | | 6z+12=5z+11 | | 3x-x-4x=18 | | -6(5+r)=12 | | 4s+3p=tp-3 | | (x^2)+2x+1=5 | | Solvex-8y=15fory | | S+s(3)=28 | | (2u)(3x^3)(7u^7x^3)=0 | | (2x+3)+(3x+2)=180 | | 4*2k=12 | | 0.2x-0.7x-8=7 | | (2x+3)+(3x+2)=360 | | -6(y-4)=-5y-9 | | 2b-3a=1 | | x(f)=x^4-10x^2+9 | | 5z-0.7=6z | | 7-(2x-2)=6-3x | | 0.02(y-9)+0.10y=0.20y-0.1 | | 4e^2x+6=25 | | 5z+5=6z-9 | | 7(3x+4)=3(x-6)+4 | | 1.2m+7.5m=63 | | (x)=x^4-10x^2+9 | | 35+10=20+x | | 9-(4y-7)=6-5y | | 35=52-y | | 3e^3x+4=6 | | 72u^3-50u=0 |